Genome‐wide association studies of multiple sclerosis. Issue 6 (31st May 2018) - Cotsapas, Chris; Mitrovic, Mitja
Abstract: Large‐scale genetic studies of multiple sclerosis have identified over 230 risk effects across the human genome, making it a prototypical common disease with complex genetic architecture. Here, after a brief historical background on the discovery and definition of the disease, we summarise the last fifteen years of genetic discoveries and map out the challenges that remain to translate these findings into an aetiological framework and actionable clinical understanding.